Your Silence Will Not Protect You - Lorde, Audre (Silver Press, 2017)
Your Silence Will Not Protect You collects the essential essays and poems of Audre Lorde for the first time, including the classic 'The Master's Tools Will Never Dismantle the Master's House'. A trailblazer in intersectional feminism, Lorde's luminous writings have inspired a new generation of thinkers and writers charged by the Black Lives Matter movement. Her lyrical and incisive prose takes on sexism, racism, homophobia, and class; reflecting struggle but ultimately offering messages of hope that remain ever-more trenchant today. Also a celebrated poet, Lorde was New York State Poet Laureate until her death; her poetry and prose together produced an aphoristic and incomparably quotable style, as evidenced by her constant presence on many Women's Marches against Trump across the world. This beautiful edition honours the ways in which Lorde's work resonates more than ever thirty years after they were first published.
English
Keywords: HN1-995 Social history and conditions; Human condition